PAI Learning Evaluation Design - Edi Prasetyo; Supardi Ritonga; Nur’aina Nur’aina; Sri Norafiza (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
In Islamic Religious Education (PAI), evaluation is essential to improve the standard of teaching and learning. The purpose of this article is to provide a comprehensive understanding of PAI learning evaluation design, which includes the objectives, tools, methods, and interpretation of evaluation findings. To develop the essential components of evaluation design, this article uses a literature study approach to collect and examine various related sources, such as e-books, scientific articles, and research papers. Evaluation serves as a measure of student understanding and as useful feedback for teachers who want to improve their teaching. Applying the concepts of validity, reliability, and objectivity at every level of evaluation design is essential in this situation, as is being aware of the variations in student characteristics. It is hoped that teachers can meet students' needs and develop more successful tests by having a thorough understanding of this evaluation approach. Thus, evaluation can play a major role in shaping the morality and character of the future generation of this country in accordance with Islamic principles.